Transforming growth factor‐β (TGF‐β) expression is increased in the subsynovial connective tissues of patients with idiopathic carpal tunnel syndrome. Issue 1 (9th September 2013) - Chikenji, Takako; Gingery, Anne; Zhao, Chunfeng; Passe, Sandra M.; Ozasa, Yasuhiro; Larson, Dirk; An, Kai‐Nan; Amadio, Peter C.
ABSTRACT Non‐inflammatory fibrosis of the subsynovial connective tissue (SSCT) is a hallmark of carpal tunnel syndrome (CTS). The etiology of this finding and its relationship to the development of CTS remain poorly understood. Recent studies have found that transforming growth factor‐β (TGF‐β) plays a central role in fibrosis. The purpose of this study was to investigate the expression of TGF‐β and connective tissue growth factor (CTGF), a downstream mediator of TGF‐β, in the pathogenesis of CTS. We compared SSCT specimens from 26 idiopathic CTS patients with specimens from 10 human cadaver controls with no previous diagnosis of CTS. Immunohistochemistry was performed to determine levels TGF‐β1, CTGF, collagen 1(Col1) and collagen 3 (Col3) expression. TGF‐β1 (p < 0.01), CTGF (p < 0.01), and Col3 (p < 0.01) were increased in SSCT of CTS patients compared with control tissue. In addition, a strong positive correlation was found between TGF‐β1 and CTGF, (R2 = 0.80, p < 0.01) and a moderate positive correlation between Col3 and TGF‐β1 (R2 = 0.49, p < 0.01). These finding suggest that there is an increased expression of TGF‐β and CTGF, a TGF‐β regulated protein, and that this TGF‐β activation may be responsible for SSCT fibrosis in CTS patients. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:116–122, 2014.